The Bruno Snell’s forgotten proposal - Viana, Amadeu (Círculo de Lingüística Aplicada a la Comunicación, 2018)
In this paper we rescue La estructura del lenguaje (1971 [1952]), a singular work by Bruno Snell, which deals with the origins of grammar, on the basis of semiotic and cognitive parameters. His contribution follows the trail of the founders of cognitive anthropology, by considering human languages as the outcome of action and communication; however, Snell go after the steps of grammatical formation through relevant philological data concerning Indoeuropean varieties, and here lies the interest of his proposal. His idea of modi significandi rooted in basic communicative practices, which articulate themselves into the different grammatical and syntactic levels, lets assimilate his work to Peircean semiotics, and even beyond, to contemporary biosemiotics. Towards the end of this study, Snell’s contribution is compared to that of his contemporary Benjamin L. Whorf, and it is remarked how both authors could be of interest in order to understand the primitive strata in human languages and their persistence in present-day varieties.
Keywords: grammar; evolution; indoeuropean; biosemiotics